2016
DOI: 10.18276/miz.2016.44-19
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of the Marketing Strategy of a Healthy Food Retailer – a Case Study of the Słoneczko Shop in Łódź

Abstract: Słowa kluczowe: zdrowa żywność, żywność ekologiczna, strategia marketingowa, e-commerce, dystrybucja wielokanałowa Streszczenie. W artykule dokonano analizy wybranych aspektów strategii marketingowej firmy sprzedającej tzw. zdrową żywność w modelu dystrybucji wielokanałowej. Badania obejmowały wywiad pogłębiony z właścicielką sklepu Słoneczko i analizę prezentacji jej oferty w internecie. O doborze asortymentu decyduje skład, jakość i cena. Wśród klientów przeważają osoby z dolegliwościami zdrowotnymi. Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Baer-Nawrocka and Szalaty (2017) concluded that the main motives behind consumers’ decision to purchase organic products are health considerations and the high quality of the products offered. This is demonstrated by numerous studies conducted among different groups of respondents indicating that health benefits are the most important rationale for purchasing organic food, which confirms that consumers are convinced of the health-promoting qualities of organic products [ 70 , 71 , 72 , 73 ]. On the other hand, concern for the environment as a reason for purchasing organic food was rated by consumers as an unimportant factor [ 74 ].…”
Section: Resultsmentioning
confidence: 61%
“…Baer-Nawrocka and Szalaty (2017) concluded that the main motives behind consumers’ decision to purchase organic products are health considerations and the high quality of the products offered. This is demonstrated by numerous studies conducted among different groups of respondents indicating that health benefits are the most important rationale for purchasing organic food, which confirms that consumers are convinced of the health-promoting qualities of organic products [ 70 , 71 , 72 , 73 ]. On the other hand, concern for the environment as a reason for purchasing organic food was rated by consumers as an unimportant factor [ 74 ].…”
Section: Resultsmentioning
confidence: 61%
“…The experience of French eco-food distributors shows that success is possible in this field. Its sources can be seen in: personalisation and emphasising the pro-health activity of organic food, especially among young consumers with a high awareness level (Grzybowska-Brzezińska, 2012), branding, "…centralisation and standardisation in the intra-organisational network structure…" (Bryła, 2016) and in developing stable relations with suppliers and customers (creating a so-called "partnership brand"). The study conducted by Witek and Kuźniar (2021) shows that a greater interest in healthy nutrition and in buying organic food was demonstrated by younger female consumers, which was also confirmed by this study.…”
Section: Results Of the Researchmentioning
confidence: 99%
“…Reaching this group of consumers can be facilitated by promoting eco-food by cooking bloggers (Bryła, 2015). The "…effect of synergy and complementarity between the online shop and a traditional one…" plays an important role in the process (Bryła, 2016). Development of the organic food market is affected by some limitations, e.g.…”
Section: Results Of the Researchmentioning
confidence: 99%